STRESS CORROSION CRACKING SAMBUNGAN LAS CDW SS 316L DAN ASTM A36 DALAM VARIASI SUHU LINGKUNGAN KOROSIF FeCl2 - Angga Saputra; Femiana Gapsari; Djarot B. Darmadi (Jurnal Rekayasa Mesin, 2022)
Stress Corrosion Cracking (SCC) is known as a trigger for material failure, especially in Dissimilar Metal Welding (DMW). Although DMW promises wide application in structural design, it is found that there is high SCC mitigation making it prone to failure. Capacitor Discharge Welding (CDW) is one of the best dissimilar metal welding methods. This article observes the weld joints of CDW ASTM A36 and SS 316L against the phenomenon of SCC in a corrosive environment temperature variation of FeCl2 0.5 Molar (30, 40, and 50 0C). The results of the Constant Load Test (CLT) show that the welding threshold strength has decreased significantly due to the increase in the galvanic corrosion current which increases at high temperatures. The stress threshold of specimen T1 with a temperature variation of 30 0C K1cc 360 MPa, the specimen T2 produces a threshold of 216 MPa and the specimen T3 with 144 MPa. It can be concluded that changes in the temperature of the corrosive environment accelerate the galvanic reaction which accelerates the occurrence of corrosiveness in the weld joint. SEM/EDS photo evaluation provides a perfect picture of the corrosive distribution of the fracture surface. At the highest temperature of 50 0C, the surface corrosive rate causes a lot of bubbles and porous pores in the weld fracture, this causes the connection threshold stress to weaken.